Privatization and mergers in mixed oligopoly models - Mendez, Jose (Estudios de Economía, 2016)
The aim of this paper is to complement the existing literature on horizontal mergers, by setting a Cournot mixed oligopoly model. Specifically, the merger paradox is qualified by proving that a merger could be profitable for the merging firms even if it does not include most market firms. Furthermore, it is proved that a merger can only be welfare improving if the degree of privatization of the public firm is low enough.